2022
DOI: 10.1021/acscentsci.2c00501
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Substrate Promiscuity of a Radical S-Adenosyl-L-methionine RiPP Maturase toward Intramolecular Peptide Cross-Linking Applications

Abstract: Radical S-adenosyl-l-methionine (RS) enzymes operate on a variety of substrates and catalyze a wide range of complex radical-mediated transformations. Radical non-α-carbon thioether peptides (ranthipeptides) are a class of ribosomally synthesized and post-translationally modified peptides (RiPPs). The RS enzyme PapB catalyzes the formation of thioether cross-links between Cys/Asp (or Cys/Glu) residues located in six Cys-X3-Asp/Glu motifs. In this report, using a minimal substrate that contains a single cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…We had previously shown that PapB is capable of crosslinking peptides where the Cys and Asp residues are adjacent, as well as those separated by up to six residues. 35 This suggests a model for recognition of the substrate where the active site recognizes the thiol and carboxylate moieties of the substrate only and that the remainder of the substrate, apart from the leader sequence, does not serve a role in recognition. This was further underscored by the ability to replace even the Cys and the Asp residues with D-amino acids and generate thioether cross-links in those substrates.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously shown that PapB is capable of crosslinking peptides where the Cys and Asp residues are adjacent, as well as those separated by up to six residues. 35 This suggests a model for recognition of the substrate where the active site recognizes the thiol and carboxylate moieties of the substrate only and that the remainder of the substrate, apart from the leader sequence, does not serve a role in recognition. This was further underscored by the ability to replace even the Cys and the Asp residues with D-amino acids and generate thioether cross-links in those substrates.…”
Section: ■ Discussionmentioning
confidence: 99%
“…37 In our previous report, we demonstrated that PapB will cyclize Cys and Asp side chains that are adjacent as well as those separated by up to six residues. 35 Epimeric peptide substrates bearing D-configured Cys and Asp residues are also suitable for cyclization by PapB. Leveraging this tolerance, we generated a thioether containing analog of the FDA-approved drug octreotide, with a Cys-Glu cross-link replacing the disulfide in a threonine capped peptide.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The previously reported correction factor for the Bradford assays was used in determining concentration and stoichiometry. 49 Amino Acid Analysis and Iron Concentration Determination of Tte1186. The iron content of WT Tte1186 as well as the Fe−S cluster knockouts was established as documented previously.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“… 10 , 11 Similarly, RiPP enzymes possess a recognition element that can be used to guide a defined leader sequence to different active sites for transformation. 90 Driven by the high reactivity of the initial Ado· radicals and subsequent substrate promiscuity that this can entail, 91 a huge range of possibilities for new types of transformation is opened up if different active sites can be paired with different recognition elements in a modular fashion.…”
Section: Manipulating the Architecturementioning
confidence: 99%
“…Nature has already demonstrated this modular construction with some of the newly structurally characterized B 12 -AdoMet radical enzymes, which have discrete but integrated motifs to carry out dual chemistries. , Similarly, RiPP enzymes possess a recognition element that can be used to guide a defined leader sequence to different active sites for transformation . Driven by the high reactivity of the initial Ado· radicals and subsequent substrate promiscuity that this can entail, a huge range of possibilities for new types of transformation is opened up if different active sites can be paired with different recognition elements in a modular fashion.…”
Section: Manipulating the Architecturementioning
confidence: 99%